Case Report: Hepatic sarcoidosis-like reaction from neoadjuvant pembrolizumab in early-stage triple-negative breast cancer - Tan, Yujing; Wang, Yu; Liu, Xiaoyan; Ma, Qin; Zeng, Cheng; Zhu, Aihua; Sun, Xiaoying; Ma, Fei; Wang, Jiani (Frontiers in Immunology, 2025)
Drug-induced sarcoidosis-like reaction (DISR) is a rare adverse event associated with immunotherapy. Currently, there is no standardized treatment protocol for DISR linked to immune checkpoint inhibitors (ICIs). This study presents a case of an early-stage triple-negative breast cancer (TNBC) patient who developed hepatic sarcoidosis-like reactions during neoadjuvant pembrolizumab therapy. We provide an overview of ICI-induced sarcoidosis-like reactions in cancer patients, including incidence, mechanisms, clinical manifestations, treatment, and prognosis. Additionally, we discuss the significance of one-year adjuvant immunotherapy for early-stage TNBC patients who achieved pathological complete response after neoadjuvant therapy, offering insights for individualized therapeutic strategies in this population.